Peranan Credit Union Sebagai Lembaga Keuangan Mikro Dalam Mengantisipasi Pengeluaran Household Life Cycle Anggotanya : Studi Kasus Credit Union Bererod Gratia - Barek, Laura Florensia (UI Scholars Hub, 2013)
This research aims to describe the implementation process of micro credit and the roles of Credit Union as a microfinance institution (MFI) in order to anticipate member’s household life cycle expenditure. The study was conducted using a qualitative approach to the type of case study research. The research took place and informants at Credit Union Bererod Gratia (CUBG), Blok Q, South Jakarta. Based on this research, it is known that Credit Union as a MFI is very open, especially for poor people who have a small business. Credit Union is also useful for the changing of its member’s economic condition. Therefore, the expenses of the life cycle can be fulfilled by financial products support that offers by CUBG.